USAWEB: An Usability Metrics to Measure the Online Store Consumer's Purchase Experience - García-Salirrosas, Elizabeth Emperatriz (2022)
The study proposes to create and evaluate the validity and reliability of a scale that allows us to measure the usability of web pages for electronic commerce called USAWEB (web usability), the referred scale is composed of 10 items which makes it an easy-to-apply instrument. The pilot test consisted of 422 participants who reported making purchases online. The items were formulated after having carried out an exhaustive review of the literature to later be evaluated by experts who guaranteed the content of the construct. Exploratory and confirmatory factor analyzes were applied to evaluate the proposed model, the results revealed a one-dimensional scale with a good fit of the model that met all the CMIN, DF, CMIN/DF, CFI, SRMR, RMSEA and PClose indicators satisfactorily. In this way, this scale allows the authors to provide the scientific and business community with a reliable instrument to be applied both in future research that seeks to measure the level of usability of web pages intended for electronic commerce.